CONTEMPORARY AND EMERGING TREATMENT STRATEGIES FOR GLIOBLASTOMA: INTEGRATION OF SURGICAL, LOCAL, AND MOLECULAR APPROACHES - Jaruga, Paulina; Jachimczak , Ewa; Gąsiorowska, Vanessa; Grodkowska-Szukała, Karolina; Paczyna, Julia; Wojtanowska, Ewa; Kozicka, Julia; Mazur, Marcin; Michalak, Mateusz; Smyczyńska, Natalia (International Journal of Innovative Technologies in Social Science, 2026)
Glioblastoma is the most common and most aggressive primary malignant tumor of the central nervous system in adults and remains associated with a very poor prognosis despite multimodal treatment. The current standard of care consists of maximal safe surgical resection followed by radiotherapy and temozolomide-based chemotherapy; however, the effectiveness of this strategy is limited by marked tumor heterogeneity, the infiltrative growth pattern, the presence of the blood–brain barrier, and the immunosuppressive tumor microenvironment. The aim of this paper is to review current standards of GBM treatment as well as emerging therapeutic strategies under development. Analysis of the available evidence indicates that novel approaches such as intraoperative 18F-FET PET, intraoperative radiotherapy, local temozolomide delivery using hydrogel-based systems, intranasal drug administration, NanoTherm® therapy, and CAR-T immunotherapy may increase treatment precision, improve local tumor control, and partially overcome the limitations of systemic therapy. However, most of these methods remain investigational or experimental, and their actual impact on overall survival requires further validation. The integration of advanced imaging, local treatment modalities, and molecularly targeted therapies appears to be the most promising direction for future GBM management.